Mountain Meadows dacite : Oligocene intrusive complex that welds together the Los Angeles Basin, northwestern Peninsular Ranges, and central Transverse Ranges, California - McCulloh, Thane Hubert, 1926-; Beyer, Larry A.; Morin, Ronald W.; Geological Survey (U.S.). ([Reston, Va.] : U.S. Dept. of the Interior, U.S. Geological Survey ; Denver, CO : USGS Information Services [distributor], 2001)
A distinctive suite of dacitic rocks is shown to transect major tectonic boundaries in the San Gabriel Mountains region, thereby constraining the amount of late Cenozoic offset on several strike-slip faults.
Shipping list no.: 2002-0081-P.
Includes bibliographical references (p. 26-31).
Also available via Internet from the USGS Web site (PDF file). Address as of 5-16-02: http://geopubs.wr.usgs.gov/prof-paper/pp1649/pp1649.pdf; current access is available via PURL.
Keywords: Dacite -- California -- San Gabriel Mountains Region; Rocks, Igneous -- California; Fault zones -- California; Intrusions (Geology) -- California; Geology, Stratigraphic -- Oligocene; Geology, Structural -- California -- San Gabriel Mountains Region